To solve the equation \(\frac{(x + 16)^2}{9} = 7\), follow these steps:
-
Multiply both sides by 9 to eliminate the fraction: \[ (x + 16)^2 = 7 \cdot 9 \] \[ (x + 16)^2 = 63 \]
-
Take the square root of both sides: \[ x + 16 = \pm \sqrt{63} \]
Since \(\sqrt{63} = \sqrt{9 \times 7} = 3\sqrt{7}\), we can rewrite this as: \[ x + 16 = \pm 3\sqrt{7} \]
-
Solve for \(x\) by subtracting 16 from both sides: \[ x = -16 \pm 3\sqrt{7} \]
Thus, the solutions for \(x\) are: \[ x = -16 + 3\sqrt{7} \quad \text{and} \quad x = -16 - 3\sqrt{7} \]